Equine flexor tendon imaging part 1: Recent developments in ultrasonography, with focus on the superficial digital flexor tendon. (December 2021) - Ehrle, Anna; Lilge, Svenja; Clegg, Peter D.; Maddox, Thomas W.
Highlights: Power Doppler and contrast add value to B-mode ultrasonography in equine flexor tendon imaging. Elastography may be used as a monitoring tool in equine flexor tendinopathy. Tendon ultrasound tissue characterisation can detect training induced tendon micro-damage. Abstract: Flexor tendon injuries are a major cause of lameness in performance horses and have considerable impact on equine welfare and the wider horse industry. Ageing and repetitive strain frequently cause varying degrees of tendon micro-damage prior to the recognition of clinical tendinopathy. Whilst B-mode ultrasonography is most commonly utilised for detection and monitoring of tendon lesions at the metacarpal/metatarsal level, the emphasis of recent research has focused on the identification of subclinical tendon damage in order to prevent further tendon injury and improve outcomes. The introduction of elastography, acoustoelastography and ultrasound tissue characterisation in the field of equine orthopaedics shows promising results and might find wider use in equine practice as clinical development continues. Based on the substantial number of research studies on tendon imaging published over the past decade this literature review aims to examine the currently used ultrasonographic imaging techniques and their limitations, and to introduce and critically appraise new modalities that could potentially change the clinical approach to equine flexor tendon imaging.